Tumor‐derived exosomes and microvesicles in head and neck cancer: Implications for tumor biology and biomarker discovery. Issue 10 (3rd June 2013) - Principe, Simona; Hui, Angela Bik‐Yu; Bruce, Jeff; Sinha, Ankit; Liu, Fei‐Fei; Kislinger, Thomas
Abstract : Exosomes and microvesicles (MVs) are nanometer‐sized, membranous vesicles secreted from many cell types into their surrounding extracellular space and into body fluids. These two classes of extracellular vesicles are regarded as a novel mechanism through which cancer cells, including virally infected cancer cells, regulate their micro‐environment via the horizontal transfer of bioactive molecules: proteins, lipids, and nucleic acids (DNA, mRNA, micro‐RNAs; oncogenic cargo hence often referred to as oncosomes). In head and neck cancer (HNC), exosomes and MVs have been described in Epstein Barr Virus (EBV)‐associated nasopharyngeal cancer (NPC), as well as being positively correlated with oral squamous cell carcinoma (OSCC) progression. It has therefore been suggested that HNC‐derived vesicles could represent a useful source for biomarker discovery, enriched in tumor antigens and cargo; hence fundamentally important for cancer progression. This current review offers an overall perspective on the roles of exosomes and MVs in HNC biology, focusing on EBV‐associated NPC and OSCC. We also highlight the importance of saliva as a proximal and easily accessible bio‐fluid for HNC detection, and propose that salivary vesicles might serve as an alternative model in the discovery of novel HNC biomarkers.